Evaluating the effectiveness of mindfulness-based sexual therapy for women with sexual dysfunction: A systematic literature review - Eka, Grace; Tondok, Marselius Sampe (Jurnal Ilmiah Psikologi Terapan, 2024)
This study aimed to explore and synthesize the effectiveness of mindfulness-based therapy in addressing sexual dysfunction that adversely impacts the quality of women sexual relationships with the partners. Systematic Literature Review (SLR) methodology was used based on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. In this study, a systematic literature search was conducted on integrated databases, namely SagePub, Science Direct, Springer, and PubMed, for articles published between 2014 and 2023. The search terms used were "mindfulness sexual therapy" and a total of eight articles were selected based on predefined inclusion and exclusion criteria. The results showed that mindfulness-based therapy could be a valuable and promising intervention for enhancing sexual function in women with sexual dysfunction and low relationship quality. Future studies should conduct similar analyses with male subjects.